Using formative evaluation to improve uptake of a web-based tool to support antimicrobial stewardship. - Zaidi, S. T. R.; Thursky, K. A. (Journal of Clinical Pharmacy & Therapeutics, 2013)
What is known and objective Web-based decision support tools have rationalized prescribing of antimicrobials in healthcare settings. Clinicians' acceptance of decision support tools is one of the important factors that determine successful implementation of such tools. This study evaluated the impact of a formative evaluation on the uptake of a web-based antibiotic computerized decision support system ( CDSS) by clinicians at a university teaching hospital. Methods Semi-structured qualitative interviews were conducted with junior and senior doctors and pharmacists. Interviews were transcribed verbatim and reviewed to identify barriers surrounding clinicians' use of the antibiotic CDSS. Recommendations were made to the development team of the studied system regarding system modifications and the implementation strategy. An automated log of the clinicians' use of antibiotic CDSS was generated before and after the formative evaluation. Results Interviews of 42 clinicians identified several barriers related to contents and implementation strategy of the antibiotic CDSS. Important differences were observed between senior and junior doctors about various aspects of the antibiotic restriction strategy and applicability of antibiotic CDSS in specialized clinical areas. Recommendations from the formative evaluation study resulted in significant modifications to the contents and implementation strategy of the antibiotic CDSS. A significant increase in uptake of the antibiotic CDSS by clinicians was observed following the formative evaluation. What is new and conclusion The formative evaluation approach during the implementation period of the studied antibiotic CDSS increased clinicians' uptake of the system. Formative evaluation may be recommended as a routine strategy to implement future CDSS and related clinical computing applications in hospital settings.